Surface creep rate of the southern San Andreas fault modulated by stress perturbations from nearby large events - Xu, Xiaohua (2019)
A major challenge for understanding the physics of shallow fault creep has been to observe and model the long‐term effect of stress changes on creep rate. Here we investigate the surface creep along the southern San Andreas fault (SSAF) using data from interferometric synthetic aperture radar spanning over 25 years (ERS 1992–1999, ENVISAT 2003–2010, and Sentinel‐1 2014–present). The main result of this analysis is that the average surface creep rate increased after the Landers event and then decreased by a factor of 2–7 over the past few decades. We consider quasi‐static and dynamic Coulomb stress changes on the SSAF due to these three major events. From our analysis, the elevated creep rates after the Landers can only be explained by static stress changes, indicating that even in the presence of dynamically triggered creep, static stress changes may have a long‐lasting effect on SSAF creep rates.